From tRNA to miRNA: RNA‐folding contributes to correct entry into noncoding RNA pathways. Issue 15 (21st July 2016) - Hasler, Daniele; Meister, Gunter
Abstract : Although RNA are synthesized as single‐stranded molecules, most of them are characterized by extensive secondary structures. Two RNA that require distinct folding for biogenesis and function are miRNA and tRNA. While miRNA are processed from hairpin‐containing precursors, tRNA are folded into characteristic L‐shaped structures. In addition, tRNA and their precursors are a rich source of RNA fragments. Recent findings suggest that their production might be determined by structural characteristics of the tRNA substrates. Importantly, correct folding of pre‐tRNA is assisted by the Lupus autoantigen La, an RNA chaperone. In this context, La interacts with pre‐tRNA to prevent alternative foldings leading to mis‐channeling into the miRNA pathway. Thus, RNA chaperones also function as gatekeepers for correct RNA pathway selection. Abstract :